Pengelolaan Aset Tanah Pemerintah Kabupaten Purbalingga - Yosinta Kingkin Nurrobani; Wahid Abdurrahman (Journal of Politic and Government Studies, 2018)
The management of Regional Property is done through the regulated mechanism to make the implementation optimal and can be accounted for its existence. The management of land assets is still facing many problems for it is a vital object of the implementation of government operations. The problem encountered in the land assets management of Purbalingga Government is in 2016 from the aspect of legal safeguards which is in the process of land assets certification. This research aims to discover and analyze the land assets management of Purbalingga Government that is examined from the aspect of planning, organization, movement, supervision, and evaluation. The theory used in this research is theory of government management according to Dharma Setyawan Salam. This research uses qualitative method. The method of data collection used in this research are interview and documentation.Land assets management of Purbalingga Government tends not to be good. The Planning is divided into four aspects, they are procurement planning, maintenance planning, utilization planning, removal planning and land assets security planning. The Organization is based on Regulation of the Minister of Home Affairs Number 19 of 2016 about Guidelines on the Management of Regional Property. The Movement is done through internal and external coordination. The Supervision consists of government internal control from the Inspectorate of Purbalingga Regency and external control from The Audit Board Representation of Central Java Province. The Evaluation is done in the form of the balance of planned needs and its implementation of the land assets management of Purbalingga Government.The result of this research shows that the land assets management of Purbalingga Government has been done through the proper mechanism, but in its implementation, there are still found several problems in the aspect of planning and coordination built up in land assets management of Purbalingga Government.Keywords: Assets, Management, Regional Government